Visible-Light-Mediated Photocatalytic Oxidative C–C Bond Cleavage of Geminal Diazides: An Approach to Oxamates - Katta, Narenderreddy; Murugan, Arumugavel; Sharma, Sonika; Sharada, Duddu S. (SynOpen, 2021)
Photoredox catalysis has received great attention in both academia and industry and remarkable progress has been made over the past decade. Now, it has been shown that a visible-light-mediated oxidative C–C bond cleavage of geminal diazides can be induced by organic dye catalysis for the synthesis of oxamates. A mechanistic study, confirmed by control experiments, indicates that this proceeds through single-electron transfer (SET). This methodology can be applied to convert a wide array of geminal diazides into oxamates.
Keywords: photoredox; oxamates; C–C cleavage